Divine Agency and Human Agency in the Sacramentology of T. F. Torrance - Irving, Alexander J. D. (The Evangelical quarterly, 2018)
Torrance's sacramentology is characterised by the unequal collaboration of divine agency and human agency. The sacraments of the Church derive their content and significance from the act of God through the incarnate Word (the primary Sacrament), and through the sacraments of the Church, Christ himself ministers to his Church. Ultimately, this collaborative sacramentology is conditioned by its being framed within the conceptual structure of the hypostatic union, which Torrance holds to be the normative example of the divine-human relationship. The hypostatic union thus provides the necessary unitive framework for sacramental theology. Within this unitive frame, Torrance presents baptism and the Eucharist as ecclesial acts which have their presupposition and content in the act of God in Jesus Christ.